2021
DOI: 10.1128/aac.00169-21
|View full text |Cite
|
Sign up to set email alerts
|

Human Tissue Distribution of Anidulafungin and Micafungin

Abstract: Concentrations of anidulafungin and micafungin were determined in eight different tissues obtained during autopsy of four deceased who had been treated with anidulafungin and of seven who had obtained micafungin. The highest amounts were recovered from liver with anidulafungin concentrations of 11.01 – 66.50 μg/g and micafungin levels of 0.36 – 5.53 μg/g (0.65 μg/g 30 days after the last administration). The lowest anidulafungin levels were measured in skeletal muscle, lowest micafungin concentrations in kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
3
0
0
Order By: Relevance
“…Micafungin showed comparable penetration into the macrophages to clofazimine despite being used at a lower concentration. This result was consistent with previously reported strong penetration and accumulation of echinocandins in macrophages in clinical settings [39][40][41] and indicated that ICG retain high viability even though the intracellular micafungin concentration reaches >100 µM, or 256X of the MIC, by 0.5 h pst (Fig. 1g).…”
Section: Micafungin Efficiently Penetrates Into Macrophages and Rapid...supporting
confidence: 93%
“…Micafungin showed comparable penetration into the macrophages to clofazimine despite being used at a lower concentration. This result was consistent with previously reported strong penetration and accumulation of echinocandins in macrophages in clinical settings [39][40][41] and indicated that ICG retain high viability even though the intracellular micafungin concentration reaches >100 µM, or 256X of the MIC, by 0.5 h pst (Fig. 1g).…”
Section: Micafungin Efficiently Penetrates Into Macrophages and Rapid...supporting
confidence: 93%
“…In general, the burden was the highest in the spleen, followed by the kidney, and the liver had the least burden. In fact, this observation is in line with a previous study documenting liver and kidney containing the highest and the lowest micafungin concentrations from autopsy samples, respectively ( 25 ). Similarly, we previously showed that caspofungin, not micafungin, had a lower concentration in the spleen but still higher than the MIC, compared to kidney ( 18 ).…”
Section: Resultssupporting
confidence: 92%
“…Micafungin showed comparable penetration into the macrophages to clofazimine despite being used at a lower concentration. This result was consistent with previously reported strong penetration and accumulation of echinocandins in macrophages in clinical settings (38)(39)(40) and indicated that ICG retain high viability even though the intracellular micafungin concentration reaches >100 µM, or 256X of the MIC, by 0.5 hour pst (Figure 1g).…”
Section: Micafungin Efficiently Penetrates Into Macrophages and Rapid...supporting
confidence: 93%